2016
DOI: 10.1080/19415257.2016.1216883
|View full text |Cite
|
Sign up to set email alerts
|

The value of collaborative rounds for teacher professional learning in Australia

Abstract: Teacher professional learning (PL) is increasingly being viewed by governments, bureaucracies, and school systems as an important vehicle for improving teaching quality and effectiveness. This new enthusiasm, however, has to be set against a history of professional development in schools that was of marginal quality and benefit. In response to this history, education authorities are interested in PL that emphasises collaborative, relevant and authentic opportunities for teachers. This paper reports a study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Hargreaves et al (2013) argued in favour of teacher involvement in planning professional development programmes so that teachers' needs are reflected. Mansfield and Thompson (2016) argued for teacher involvement in agenda-setting to increase ownership and commitment to professional development initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hargreaves et al (2013) argued in favour of teacher involvement in planning professional development programmes so that teachers' needs are reflected. Mansfield and Thompson (2016) argued for teacher involvement in agenda-setting to increase ownership and commitment to professional development initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the initiative to improve teacher professional practice is placed in the teacher's hands, rather than administrators and/ or external experts -more akin to a doctor who prepares remedies for him-or herself. Recent research has shown that classroom practice improves when teachers are given the autonomy to find solutions to challenges they encounter in their practice (Gore & Rosser, 2020;Govender, 2018;Mansfield & Thompson, 2016;Rincon-Gallardo & Fullan, 2016;Stacy, 2013). When teachers are involved in their own professional development, their confidence with, ownership of and commitment to new ideas and school reform increase.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning teachers also highlight the importance of having opportunities to be with other teachers to dialogue, to observe, to co-plan, to have time to establish relationships with experienced teachers and mentors (Reeves 2008, Mansfield andThompson 2017). Bieler (2012, p. 47) speaks of 'crafting community' through sharing friendship and ideas:…”
Section: Induction and Continuing Professional Development: A Brief Rmentioning
confidence: 99%
“…The process of identifying training needs is directed, which directs training in the right direction to meet the needs, desires, and interests of teachers, therefore, it is necessary to determine the needs of employees before starting any training process to reach the required results (Lindqvist & Nordӓnger 2016;Mansfield & Thompson 2017). Training increases the efficiency of teaching, which is a measure of the teacher's success in performing his task and works to increase the return on education in different situations within the educational process (Meissel, Parr & Timperley, 2016).…”
Section: Introductionmentioning
confidence: 99%